(untitled) (Archive of Conferences, 2021)
Learning Management System (LMS) is an application that provides a comprehensive set of tools for educators to manage teaching and learning. Considering that the number of students is growing and education is expanding in various dimensions and modes of delivery, institutions or individual instructors are seeking for additional LMS tools and services. The aim of this paper is to present an experience of adding a new testing tool to an existing LMS. The evolution of the LMS solution at SEE University is provided, together with the initial set of LMS modules, the benefits of modular approach as well as specific details for the testing module itself.